2021
DOI: 10.15252/embj.2020107134
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA VEAL2 regulates PRKCB2 to modulate endothelial permeability in diabetic retinopathy

Abstract: Long non‐coding RNAs (lncRNAs) are emerging as key regulators of endothelial cell function. Here, we investigated the role of a novel vascular endothelial‐associated lncRNA (VEAL2) in regulating endothelial permeability. Precise editing of veal2 loci in zebrafish (veal2gib005Δ8/+) induced cranial hemorrhage. In vitro and in vivo studies revealed that veal2 competes with diacylglycerol for interaction with protein kinase C beta‐b (Prkcbb) and regulates its kinase activity. Using PRKCB2 as bait, we identified fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 92 publications
0
47
0
Order By: Relevance
“…The functional mechanisms of lncRNAs vary; however, they can be divided into two main groups: cis -regulation and trans -transcriptional regulation ( Yan et al, 2017 ). Several lncRNAs have been discovered that affect the pathogenesis of T2D: lncRNA betaFaar regulates islet beta-cell function and survival in T2D mice; lncRNA VEAL2 targets PRKCB2 contributing to reducing hyperpermeability in a hyperglycemic animal model ( Sehgal et al, 2021 ; Zhang et al, 2021 ). This latter study suggests that lncRNA impacts the expression of genes that regulate bone mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…The functional mechanisms of lncRNAs vary; however, they can be divided into two main groups: cis -regulation and trans -transcriptional regulation ( Yan et al, 2017 ). Several lncRNAs have been discovered that affect the pathogenesis of T2D: lncRNA betaFaar regulates islet beta-cell function and survival in T2D mice; lncRNA VEAL2 targets PRKCB2 contributing to reducing hyperpermeability in a hyperglycemic animal model ( Sehgal et al, 2021 ; Zhang et al, 2021 ). This latter study suggests that lncRNA impacts the expression of genes that regulate bone mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…VEAL2 was found to be upregulated in the blood of diabetic retinopathy patients, and overexpression of the lncRNA in hyperglycemia model of HUVECs could attenuate PRKCB2-mediated hyper-permeability. A zebrafish knockout model for the ortholog veal2 caused cranial hemorrhage, which could be rescued by the PRKCB2 inhibitor Enzastaurin ( Sehgal et al, 2021 ). Aging related lncRNA AERRIE is important to maintain endothelial function and angiogenesis in vitro .…”
Section: Long Non Coding Rnas In Endothelial Functionmentioning
confidence: 99%
“…In lieu of the poor sequence conservation of lncRNAs, identification of lncRNAs in animal models can illuminate hitherto unknown regulatory angles in well studied pathways. Identification of functionally conserved human lncRNA has been exemplified in the case of lncRNAs jpx (mouse) ( Karner et al, 2020 ) and veal2 (zebrafish) ( Sehgal et al, 2021 ) even in the absence of sequence or structural conservation, albeit with a conserved interacting protein partner. This provides a framework to look beyond sequence-based conservation for identifying lncRNA candidates that regulate well-conserved pathways.…”
Section: Future Perspectives For Studying Lncrna In Bbb Functionmentioning
confidence: 99%
“…It was reported that more than 460 million adults worldwide had diabetes in 2019, and this number would rise to 700 million by 2045 ( Saeedi et al, 2019 ). Since T2DM contributes to the occurrence of harmful macrovascular and microvascular outcomes ( Sehgal et al, 2021 ; Zeng et al, 2021 ; Zhang X. et al, 2021 ; Zhao et al, 2021 ), it not only brings physical and mental pain to patients, but also leads to a major medical economic burden. Therefore, it is of great significance to explore the novel pathogenesis and treatment of T2DM.…”
Section: Introductionmentioning
confidence: 99%